Random Access Control for M2M in LTE System. (9th December 2013) - Chen, Zhide; Zeng, Yali
Abstract : With the implementation of 4G mobile networks, the number of M2M users will be much large in a cell. When massive M2M users try to randomly access simultaneously, this will impose a great influence on H2H communication. Without effective control, these M2M users will lead to a system breakdown. In this paper, we put forward a model, which allows low delay tolerance of users to have a higher priority for random access, when contending with high delay tolerance of users for limited random access resources. In this model, by controlling access rates of different delay tolerance of users, the random access success probability will be improved efficiently. In the meantime, it will achieve the highest success probability and optimize the system performance by setting optimal access rates for different delay tolerance of users. This will be a practical guide to M2M communication in LTE system.